2019
DOI: 10.1002/mrd.23136
|View full text |Cite
|
Sign up to set email alerts
|

The evolution and possible role of two Sox8 genes during sex differentiation in Japanese flounder (Paralichthys olivaceus)

Abstract: Sox8 genes, as members of the Sox family, have been studied widely in mammals. However, regulation of sox8 genes in teleosts has rarely been studied, and functional analysis of these genes in teleosts has rarely been performed. Here, two duplicates of sox8 genes were identified in Japanese flounder, Posox8a and Posox8b. The analysis of expression showed that Posox8a and Posox8b were expressed in Sertoli cells of the testis, indicating that they play important roles in development and functional maintenance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…2011) and P. olivaceus (Yu et al . 2019), suggesting that sox8 plays an important role in testicular differentiation rather than in ovary. Many reports have also suggested that sox9 plays an important role in sex differentiation during sex reversal of fish.…”
Section: Functions Of Sox Genes In Fishmentioning
confidence: 99%
See 2 more Smart Citations
“…2011) and P. olivaceus (Yu et al . 2019), suggesting that sox8 plays an important role in testicular differentiation rather than in ovary. Many reports have also suggested that sox9 plays an important role in sex differentiation during sex reversal of fish.…”
Section: Functions Of Sox Genes In Fishmentioning
confidence: 99%
“…Many studies have proved that the expression of sox8 is higher in the testis than in the ovary of fish, such as P. dabryanus (Xia et al 2010), M. anguillicaudatus (Xia et al 2011) and P. olivaceus (Yu et al 2019), suggesting that sox8 plays an important role in testicular differentiation rather than in ovary. Many reports have also suggested that sox9 plays an important role in sex differentiation during sex reversal of fish.…”
Section: Sex Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…On the 5th day after the first injection, the testis and ovaries were immediately frozen in liquid nitrogen and then stored at −80°C until RNA extraction. The injection doses and times were chosen according to our previous studies in Japanese flounder (Yu et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The Japanese flounder testis cell line used in this experiment was constructed by Yu et al (). Transient transfection assay of testis cells was performed using LipoGene™ 2000 Plus Transfection Reagent (US Everbright, Inc., Suzhou, China) following the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%